Improving nutrition through increased utilisation of local agricultural biodiversity in Kenya – the INULA initiative - Keding, G. (2014)
This poster presents the GIZ/BMZ funded INULA initiative in Western Kenya. The main objectives are to document available and accessible local food diversity on-farm, in markets and from the wild as well as seasonal changes; to determine food intake levels, dietary diversity, anthropometrics and socio-economic characteristics of mother-child pairs pre and post intervention (nutrition education); and to conduct and analyse participatory nutrition education sessions on the increased use of local food diversity for nutrient adequate complementary foods.First results show that nutrition education among caregivers is associated with increased diversity of complementary foods; at the same time no direct relationship between dietary diversity scores and farm richness was found.